ANTIPROLIFERATIVE ACTIVITY OF OCTADECA-8,10,12-TRIYNOIC ACID AGAINST HUMAN CANCER CELL LINES [Antiproliferasi Asam Oktadeka-8,10,12-triunoat Terhadap Galur Sel Kanker Manusia] - Winarno, Hendig (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Antiproliferative activity test of octadeca-8,10,12-triynoic acid isolated from parasitic plant Scurrula airopurpurea (Bl.) Dans,against four kinds of human cancer cell lines, i.e: HeLa (human cervix epitheloid carcinoma),leukemia THP1,(human peripheral blood acute monocyte).carcinoma A549 (human lung carcinoma) and lymphoma HUT78 (human cutaneous T-cell lymphoma)was carried out.The results showed that octadeca-8.10,12-triynoic acid exhibits the antiproliterative activity against four kinds of human cancer cell lines with the 1C5I, value of 0.66. 0.86, 0.99 and 2.36 mg/nil for HeLa.leukemia THP1, lung carcinoma A549,and lymphoma HUT78,respectively, lower than 4 mg/ml. which is the antiproliferative activity threshold for pure isolate or compound.